CURRENT DIRECTIONS OF RESEARCH IN INFORMATION- COMMUNICATION TECHNOLOGIES IN THE FIELD OF PEDAGOGICAL SCIENCE. - O.N. Spirin; A.V. Svietlorusova (Kherson State University, 2010)
In the publication modern research areas of information-communication technologies in pedagogical science are identified. The basic requirements of the new passport for the specialty 13.00.10 - Information and Communication Technologies in Education are described. On this specialty the defence of the degree of doctor and candidate of pedagogical science may be carried out.